Praziquantel in the cerebrospinal fluid in neurocysticercosis - A. Spina-França; L. R. Machado; J. P. S. Nobrega; J. A. Livramento; H. W. Diekmann; E. Groll; G. L. de Rezende (Arquivos de Neuro-Psiquiatria, 1985)
In 10 patients with neurocysticercosis (NC), an assessment was made of the praziquantel (PZQ) concentration in the cerebrospinal fluid (CSF), in non-deproteinized serum and in protein-free serum: before administration of the drug and the 1st., 7th. and 21st. days of oral administration (50mg/kg/day during 21 days). Samples of CSF and blood were collected three hours after the last administration of the daily total dosage, on the 1st. and 21st days; and from 2 to 6 hours after drug administration on the 7th. day. The total daily dosage was distributed into three equal parts of 1/3 each, with a 4 hours' interval between intakes, except in the last 5 cases, who on the 21st. day only were given the total daily dosage on a single administration. Results have shown dispersion in serum concentrations, which are similar to those seen in normal subjects as recorded in literature. There is a correlation between PZQ levels in the CSF and in the serum, the latter being very close to those found in protein-free serum fraction. The statistical treatment of results allowed the following considerations: PZQ concentrations in the CSF and in the protein free serum are in balance from the pharmacodynamic standpoint on the first day; this balance is maintained up to the 21st. day although at different levels from those seen on the 7th. day; on the 21st. day PZQ contents in CSF goes back to its similar values as recorded on the 1st. day, and this suggests that the participation of drug interaction factors has been reduced to non-significant levels. However, several factors can influence PZQ concentration in CSF, as absorption rate, liver first-pass effect and blood-brain barrier changes, and individual dose should be established for each patient based on drug concentration monitoring in the serum and/or in the CSF.